Impact of preheating environment on microstructural and optoelectronic properties of Cu2ZnSnS4 (CZTS) thin films deposited by spin-coating - Ahmoum H.; Chelvanathan P.; Su'ait M.S.; Boughrara M.; Li G.; Al-Waeli A.H.A.; Sopian K.; Kerouad M.; Amin N. (Academic Press, 2023)
Argon; Coatings; Copper compounds; Crystallinity; Crystallite size; Morphology; Nanocrystalline materials; Preheating; Sol-gel process; Sol-gels; Spin coating; Surface morphology; Tin compounds; Zinc compounds; CZTS; CZTS thin films; Micro-structural; Microstructural inhomogeneity; N2 atmospheres; Optoelectronic properties; Photovoltaic; Sulfurization; Thin films